The evolution of HIV-1 reverse transcriptase in route to acquisition of Q151M multi-drug resistance is complex and involves mutations in multiple domains. - Mbisa, J; Gupta, R; Kabamba, D; Mulenga, V; Kalumbi, M; Chintu, C; Parry, C; Gibb, D; Walker, SA; Cane, P; Pillay, D (2011)
BACKGROUND: The Q151M multi-drug resistance (MDR) pathway in HIV-1 reverse transcriptase (RT) confers reduced susceptibility to all nucleoside reverse transcriptase inhibitors (NRTIs) excluding tenofovir (TDF). This pathway emerges after long term failure of therapy, and is increasingly observed in the resource poor world, where antiretroviral therapy is rarely accompanied by intensive virological monitoring. In this study we examined the genotypic, phenotypic and fitness correlates associated with the development of Q151M MDR in the absence of viral load monitoring. RESULTS: Single-genome sequencing (SGS) of full-length RT was carried out on sequential samples from an HIV-infected individual enrolled in ART rollout. The emergence of Q151M MDR occurred in the order A62V, V75I, and finally Q151M on the same genome at 4, 17 and 37 months after initiation of therapy, respectively. This was accompanied by a parallel cumulative acquisition of mutations at 20 other codon positions; seven of which were located in the connection subdomain. We established that fourteen of these mutations are also observed in Q151M-containing sequences submitted to the Stanford University HIV database. Phenotypic drug susceptibility testing demonstrated that the Q151M-containing RT had reduced susceptibility to all NRTIs except for TDF. RT domain-swapping of patient and wild-type RTs showed that patient-derived connection subdomains were not associated with reduced NRTI susceptibility. However, the virus expressing patient-derived Q151M RT at 37 months demonstrated ~44% replicative capacity of that at 4 months. This was further reduced to ~22% when the Q151M-containing DNA pol domain was expressed with wild-type C-terminal domain, but was then fully compensated by coexpression of the coevolved connection subdomain. CONCLUSIONS: We demonstrate a complex interplay between drug susceptibility and replicative fitness in the acquisition Q151M MDR with serious implications for second-line regimen options. The acquisition of the Q151M pathway occurred sequentially over a long period of failing NRTI therapy, and was associated with mutations in multiple RT domains.